Genomic Evaluation of Sunflower Broomrape (Orobanche Cumana) Germplasm by KASP Assay - ALTINKUT UNCUOĞLU, AHU; AYDİN, YILDIZ (De Gruyter Open Ltd, 2018)
Orobanche cumana Wallr. is a holoparasitic plant for only sunflower, hence it is called as sunflower broomrape. Yield loss created by O. cumana which is generally 50 % can reach to 100%. In this study, it was planned to perform molecular characterization of O. cumana germplasm as nine locations of Thrace region obtained from Trakya Agricultural Research Institute by using Single Nucleotide Polymorphism (SNP) markers, widely used in plant breeding programs, in Competitive Allele Specific PCR (KASP) assay which is a fluorescent tagged allele specific PCR method based, economic, reliable and easily repeatable genotyping technology. Databases and literature were scanned to spot variations on O. cumana genome which is not known clearly. So far, four SSR (Simple Sequence Repeat) marker (Ocum-197, Ocum-006, Ocum-023 and Ocum-151) regions showing polymorphic pattern were used for searching possible SNPs. Primer pairs were designed for amplification of the regions possibly having SNPs and PCR amplifications with these primer pairs were performed and 1 candidate deletion was detected on the amplicon which was amplified by Ocum-197 SSR marker. Following, the deletion was converted to KASP primers and KASP assay was performed. The deletion marker, Del-197, has grouped the samples from nine locations in the resulting allelic discrimination plot and infestation was performed according to this grouping, As a conclusion, Del-197 is considered as a selective marker for the ability to rapidly assay allelic variation at DNA markers for O. cumana populations that have effects on infestation results were evaluated as races, F, G, H and I in Thrace region. © 2018 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: KASP; molecular characterization; Orobanche cumana; SNP markers